2021
DOI: 10.3390/sports9070097
|View full text |Cite
|
Sign up to set email alerts
|

Association and Agreement between Reactive Strength Index and Reactive Strength Index-Modified Scores

Abstract: Since the reactive strength index (RSI) and reactive strength index-modified (RSI-mod) share similar nomenclature, they are commonly referred as interchangeable measures of agility in the sports research literature. The RSI and RSI-mod are most commonly derived from the performance of depth jumping (DJ) and countermovement jumping (CMJ), respectively. Given that DJ and CMJ are plyometric movements that differ materially from biomechanical and neuromotor perspectives, it is likely that the RSI and RSI-mod measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…We also reported that RSI was associated with LM and there was a significant negative correlation between drop jump and FM, indicating excess FM is a significant factor affecting jumping ability in capoeira athletes. It is well documented that RSI is an important indicator of the stretch-shortening cycle (SSC) efficiency, defined as muscle action when active muscle lengthening is immediately followed by active muscle shortening (Louder, Thompson, & Bressel, 2021;Seiberl, Hahn, Power, Fletcher, & Siebert, 2021). For example, Flynn (Flynn, 2016) reported that RSI was negatively associated with percent FM and body weight, which is in line with the findings of the current study, indicating the role of excess body weight in jumping ability.…”
Section: Discussionsupporting
confidence: 89%
“…We also reported that RSI was associated with LM and there was a significant negative correlation between drop jump and FM, indicating excess FM is a significant factor affecting jumping ability in capoeira athletes. It is well documented that RSI is an important indicator of the stretch-shortening cycle (SSC) efficiency, defined as muscle action when active muscle lengthening is immediately followed by active muscle shortening (Louder, Thompson, & Bressel, 2021;Seiberl, Hahn, Power, Fletcher, & Siebert, 2021). For example, Flynn (Flynn, 2016) reported that RSI was negatively associated with percent FM and body weight, which is in line with the findings of the current study, indicating the role of excess body weight in jumping ability.…”
Section: Discussionsupporting
confidence: 89%
“…All three trials were performed at a given height before proceeding to the next condition. The selection of drop heights was informed by a meta-analysis [ 52 ] that reported that plyometric training interventions may include DJs performed from drop heights ranging between 0.12 and 1.10 m. Additionally, in our recent work [ 53 ], we observed that GCTs were not significantly impacted when DJs were performed from the range of drop heights included in the current investigation.…”
Section: Methodsmentioning
confidence: 95%
“…Young (1995) proposed the RSI as a measure of the ability to quickly transition from eccentric to concentric muscle contractions during jumping. The RSI is calculated as the jump height during a DJ divided by the contact time ( Louder, Thompson & Bressel, 2021 ). Improvement of the RSI can be achieved by increasing jump height and decreasing contact time.…”
Section: Discussionmentioning
confidence: 99%